PENGARUH KETEPATAN WAKTU, KEPERCAYAAN, KETELITIAN DAN ASURANSI TERHADAP KEPUTUSAN PENGGUNA JASA PPJK PADA PT. VTRANS INTERNATIONAL BATAM - Mulyadi, Mulyadi (BENING, 2019)
This study aims to obtain information about the relationship between the independent variables, namely; timeliness (X1), trust (X2), accuracy (X3), and insurance (X4) with the dependent variable, namely the Decision of PPJK service users (Y) PT. Vtrans International Batam, either individually or collectively. The population of this study were all consumers of PT. Vtrans International Batam, which in January amounted to ± 400 people. In this study, there was no classification of employee differences based on type or class status, the two types of staffing had the same treatment. Samples were taken using accidental (coincidence) techniques. By using the Slovin formula, a sample of 80 people was obtained. The results showed that there was a significant positive effect on timeliness (X1), trust (X2), accuracy (X3), and insurance (X4) on the Decision of PPJK service users (Y) as indicated by the Fcount value of 60.237. This value is much smaller than the value of Fcount at the alpha significance level of 0.05, namely 2.50, or F = 60.237